2005
DOI: 10.1002/bit.20637
|View full text |Cite
|
Sign up to set email alerts
|

Alanine 101 and alanine 110 of the alpha subunit of Pseudomonas stutzeri OX1 toluene‐o‐xylene monooxygenase influence the regiospecific oxidation of aromatics

Abstract: Saturation mutagenesis was used to generate 10 mutants of toluene-o-xylene monooxygenase (ToMO) at alpha subunit (TouA) positions A101 and A110: A101G, A101I, A101M, A101VE, A101V, A110G, A110C, A110S, A110P, and A110T; by testing the substrates toluene, o-cresol, m-cresol, p-cresol, phenol, naphthalene, o-methoxyphenol, m-methoxyphenol, p-methoxyphenol, o-xylene, and nitrobenzene, these positions were found to influence the regiospecific oxidation of aromatics. For example, compared to wild-type ToMO, TouA va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Structures of resting ToMOH and later resting T4moH revealed a contiguous ∼30 Å tunnel extending from the surface into the active site, along with both inner and intermediate chambers along the tunnel (Figure ). Mutagenesis studies with ToMOH supported the viability of its main tunnel as a catalytically relevant path for hydrocarbons, as does the crystallographic evidence showing occupation by relevant aromatic molecules. The open access of the main tunnel in T4moH crystals allowed BML to enter the active site of these crystals, while in contrast, structures of uncomplexed ToMOH and MmoH did not show aromatic molecules in the active site. , T4moD binding closed the main access tunnel in T4moH, and consequently, efforts to soak preformed T4moHD crystals with different aromatic compounds failed to yield structures with these products in the active site even if these compounds were readily entrained elsewhere in the protein.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Structures of resting ToMOH and later resting T4moH revealed a contiguous ∼30 Å tunnel extending from the surface into the active site, along with both inner and intermediate chambers along the tunnel (Figure ). Mutagenesis studies with ToMOH supported the viability of its main tunnel as a catalytically relevant path for hydrocarbons, as does the crystallographic evidence showing occupation by relevant aromatic molecules. The open access of the main tunnel in T4moH crystals allowed BML to enter the active site of these crystals, while in contrast, structures of uncomplexed ToMOH and MmoH did not show aromatic molecules in the active site. , T4moD binding closed the main access tunnel in T4moH, and consequently, efforts to soak preformed T4moHD crystals with different aromatic compounds failed to yield structures with these products in the active site even if these compounds were readily entrained elsewhere in the protein.…”
Section: Discussionmentioning
confidence: 71%
“…T4MO oxidizes the natural substrate toluene with ∼97% regiospecificity for the para position . Previous studies with T4MO and related diiron enzymes have shown that mutagenesis can alter the regiospecificity of the enzyme for reaction with toluene and other nonphysiological substrates, , in some cases with no deleterious changes in the catalytic properties of the purified enzymes ,, and in others with a broadened range of substrates reacted. , For example, G103L T4moH oxidizes toluene with ∼55% regiospecificity for the ortho position, a dramatic change from the natural enzyme, while also retaining equivalent kinetic parameters and coupling …”
mentioning
confidence: 99%
“…The biocatalyst toluene‐ o ‐xylene monooxygenase (ToMO) of Pseudomonas sp. OX1 (Cafaro et al, ; Radice et al, ) belongs to a remarkable family of bacterial multicomponent monooxygenases (BMM; Notomista et al, ) and has been shown to have a great potential for biotechnological and environmental applications (Notomista et al, ; Vardar and Wood, ; Vardar et al, ,).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these pocket residues have been the subject of several protein engineering studies and shown to influence the catalytic activity and regiospecificity (Cafaro et al, ; Fishman et al, ; McClay et al, ; Notomista et al, ; Pikus et al, ; Rui et al, ; Steffan and McClay, ; Vardar and Wood, ; Vardar et al, ). We have also previously published a summary table showing the important roles of some of these residues on catalysis (Vardar et al, ). Of these residues, F176 and F196 are especially noteworthy since these positions have not been extensively studied through saturation mutagenesis and there are only a few studies performed by rational design approach of site‐directed mutagenesis.…”
Section: Introductionmentioning
confidence: 99%